Entrepreneurial Intention in College Students: The Influence of Islamic Personality and Entrepreneurial Self-Efficacy - Akbar Rohandi, Mochamad Malik; Assyofa, Allya Roosallyn; Mahani, Nina; Handri, Handri (International Journal of Entrepreneurship and Sustainability Studies, 2025)
Today's younger generation tends to embrace freedom in their pursuits while actively developing their skills. This study investigates the factors influencing Indonesian students' intentions to become entrepreneurs from Islamic personality and entrepreneurial self-efficacy. The research examines how Islamic personality and self-belief in entrepreneurial abilities impact students' desire to start their own businesses. Universities are increasingly equipping students with entrepreneurial skills to foster job creation. By employing quantitative methods, for minimum sampling, use the green method, including a survey of 195 students, ANOVA for hypothesis testing, and a multiple linear regression equation to get a model. The study found a correlation between Islamic personality, entrepreneurial self-efficacy, and entrepreneurial intentions, with the biggest correlation between entrepreneurial self-efficacy with entrepreneurial intention. The results suggest that individuals with a stronger Islamic personality and greater confidence in their entrepreneurial capabilities are more likely to pursue entrepreneurship. The biggest impact from each dimension of each variable is syahadah from Islamic personality, build a relationship with the investor from entrepreneurial self-efficacy, and plan to start from entrepreneurial intention.